Penerapan Pendidikan Karakter Disiplin Dan Tanggung Jawab Siswa Di SD Negeri 3 Giritontro Tahun Pelajaran 2018 / 2019 - Setyawatiningsih, Kurnia (Universitas Sebelas Maret, 2020)
The character of discipline and responsibility is one of the value of character in the core competence of social attitudes to be developed to learners. The study aims to know and describe the application of the educational character discipline and responsibility of the students at SDN 3 Giritontro.This type of research is a quantitative descriptive study by survey. Sampling techniques using the inaugurate stratified cluster of random samples. The data collection technique used consisted of an interview technique, an angket, and an observation. The data is analyzed using quantitative descriptive statistics. Studies show that the application of education in character discipline and responsibility at SDN 3 Giritontro is well done. Based on research results it is best that students' behavior in applying the character discipline and responsibility need to be emphasized and should be continually related to students, so that the behavior will be better than ever.